IMPLEMENTASI PENDIDIKAN INKLUSIF DI MADRASAH IBTIDAIYAH - Huda, Misbahul; Nurlaili Dina Hafni (PREMIERE : Journal of Islamic Elementary Education, 2025)
Inclusive education represents a paradigm that emphasizes the right of every child to access equitable and quality learning regardless of physical, intellectual, social, emotional, or linguistic differences. Madrasah Ibtidaiyah (Islamic elementary schools) play a significant role in realizing inclusive education; however, the implementation remains inconsistent with national policy frameworks. This study aims to analyze key challenges and formulate evidence-based strategies to strengthen inclusive education practices within Madrasah Ibtidaiyah. The study employs a systematic-constructive literature review by analyzing academic publications, national and international policy reports, and case studies of inclusive madrasahs published between 2021 and 2025. Thematic analysis was conducted on five major aspects: policy implementation, teacher capacity, infrastructure, funding, and socio-cultural factors. The findings reveal that the main barriers to implementing inclusive education in Madrasah Ibtidaiyah include: (1) the gap between normative policy and operational practice; (2) limited teacher competence and lack of support personnel; (3) inadequate infrastructure and accessibility; (4) persistent social stigma toward children with special needs; and (5) insufficient funding and institutional incentives. Strengthening strategies include developing technical implementation guidelines, continuous professional development programs using micro-credential systems, establishing Inclusive Madrasah Teams, and integrating Islamic values as ethical and cultural foundations for inclusive practice. This study concludes that the success of inclusive education in Madrasah Ibtidaiyah depends on the harmonization of policy, teacher competency, community engagement, and Islamic spiritual values as the moral basis for educational equity. The findings contribute to policy formulation and practical models of inclusive Islamic education that are contextually relevant to Indonesia’s socio-religious landscape.